Zimbabwe : Technical Assistance Report-Report on Government Finance Statistics Technical Assistance Mission. - International Monetary Fund. Statistics Dept. (Washington, D.C. : International Monetary Fund, 2019)
This Technical Assistance Report discusses that the authorities are making some progress towards higher quality and more comprehensive Government Finance Statistics, however, sufficient information for meaningful monitoring and surveillance of the public sector in Zimbabwe should be considered a long-term goal with several remaining challenges. The government of Zimbabwe has recently embarked upon an ambitious reform program for public sector corporations, which is expected to lead to a dramatic reduction in government balance sheet risk via contingent liabilities and the direct fiscal impact arising from the high likelihood of those guarantees being called. The report also highlights that the Accountant General office should have the ability to set a standardized format and the required information for general government financial statements which are to be reported for all subsectors and ministries. The mission recommends that the authorities review compliance with Republic of Zimbabwe Public Finance Management Act of 2009 across general government subsectors, including, all local government units, Extrabudgetary Units funds and social security funds.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet